Progressive Constitutional Law Strategies to Combat Money Politics in Simultaneous Elections - Arum, Fitri (Research Horizon, 2023)
The simultaneous legislative and presidential elections in Indonesia in 2019 offer a defining opportunity to gauge the maturity of political elites and the electorate in practicing democracy. Transparent and integrity-rich elections can solidify Indonesia's democratic consolidation, while their failure may jeopardize the democratization process. Money politics, a pressing issue in Indonesian elections, undermines electoral integrity, breeds corruption, and erodes democratic principles. This paper explores the multifaceted issue of money politics and presents a progressive approach to mitigate it through constitutional and legal reforms. The study identifies key problems, such as the undue influence of wealth, the weakening of political parties, and campaign funding opacity, proposing a series of progressive regulatory measures, including transitioning to a more competitive electoral system that empowers political parties, limiting campaign funding sources to curtail the influence of affluent donors, regulating electronic campaign money transactions for enhanced transparency, prohibiting corrupt candidates from participating in elections, advocating for more inclusive and transparent coalition-building among political parties, and suggesting the revocation of election winners by the Constitutional Court in cases of election fraud like money politics. These reforms aim to address the entrenched issue of money politics, fostering fairer, more democratic, and transparent electoral processes that empower political parties and engage the electorate in the quest for democratic ideals.